Photocatalytic H2O2 and H2 Generation from Living Chlorella vulgaris and Carbon Micro Particle Comodified g‐C3N4. Issue 34 (14th October 2018) - Fu, Yijun; Liu, Chang'an; Zhang, Mengling; Zhu, Cheng; Li, Hao; Wang, Huibo; Song, Yuxiang; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract: Hydrogen production from water splitting using photocatalysts and solar energy is an ideal pathway to obtain future energy sources which are cheap and easy to industrialize. In the water splitting process, the reduction of H2 O gives H2, while H2 O oxidation produces O2 with hydrogen peroxide (H2 O2 ) in tiny amounts as a by‐product (poisoning the catalyst). It remains challenging to simultaneously produce H2 O2 and H2 within one photocatalytic system. Inspired by a biological H2 O2 generator, chlorella, the authors firstly realize the simultaneous photocatalytic water splitting and biological H2 O2 generation by a living Chlorella vulgaris and carbon micro particle (needle coke) comodified g‐C3 N4 (C‐N‐g‐C3 N4 ) photocatalyst. The C‐N‐g‐C3 N4 exhibits the optimal H2 O2 (H2 ) evolution rate of 0.98 µmol h −1 (0.84 µmol h −1 ), giving an apparent quantum efficiency of 0.86% for H2 evolution at 420 nm. In this system, the needle coke serves as cocatalyst to work as reduction sites for H2 evolution, while the living C. vulgaris plays the key role in the production of H2 O2 under the protection of g‐C3 N4 . Abstract : Living chlorella vulgaris and carbon micro particles (needle coke) co‐modified g‐C3 N4 (C‐N‐g‐C3 N4 ) exhibit H2 O2 (H2 ) evolution with 0.98 μmol h –1 (0.84 μmol h –1 ). The needle coke serves as co‐catalyst and plays the role of the reduction site for hydrogen evolution, g‐C3 N4 provides oxidation sites for partial H2 O2 evolution, and the living C. vulgaris take responsibility for improvement of H2 O2 evolution yield.